Adult Plant Slow Rusting Genes Confer High Levels of Resistance to Rusts in Bread Wheat Cultivars From Mexico - Huerta-Espino, Julio; Singh, Ravi; Crespo-Herrera, Leonardo A.; Villaseñor-Mir, Héctor E.; Rodriguez-Garcia, Maria F.; Dreisigacker, Susanne; Barcenas-Santana, Daniel; Lagudah, Evans (Frontiers in Plant Science, 2020)
Rust diseases continuously threaten global wheat production: stem rust, leaf rust and yellow rust caused by Puccinia graminis f. sp. tritici, Puccinia triticina and Puccinia striiformis f.sp. tritici, respectively. Recent studies indicated that losses from all three rusts average at least 15.04 million tons per year, which is equivalent to an annual average loss of around US $2.9 billion per year. The major focus of Mexican and worldwide breeding programs is the release of rust resistant cultivars, as this is considered the best option for controlling rust diseases. Over the last decade, increasing emphasis has been placed on genes that confer partial resistance in the adult plant stage and against a broad spectrum of rust races. We phenotyped for the three rust diseases and genotyped a set of the first-generation tall varieties developed and released in the 1940s and 1950s, the first semi-dwarfs, and other releases in Mexico, all of which showed different levels of rust resistance. Based on molecular markers, results indicate the presence of Lr34, Lr46, Lr67 and Lr68 alone or different gene combinations among the wheat genotypes. Flag leaf tip necrosis was present in all genotypes and most genotypes were positive for brown necrosis or Pseudo Black Chaff (PBC) associated with the Sr2 stem rust resistance complex. The phenotypic responses to the different rust infections indicate the presence of additional slow rusting and race-specific resistance genes. The study reveals the association of the slow rusting genes with durable resistance to the three rusts including Ug99 in varieties bred before the green revolution such as Frontera, Supremo 211, Chapingo 48, Yaqui 50, Kentana 52, Bajio 52, Bajio 53, Yaqui 53, Chapingo 53, Yaktana Tardio 54 and Mayo 54 and their descendants after intercrossing and recombination. These slow rusting genes are the backbone of the resistance in the current Mexican germplasm.